Social Enterprises, Cooperatives or Benefit Corporations? On Reconciling Profit and the Common Good in Doing Business from a Polish Perspective - Dąbrowska, Justyna (Review of European and Comparative Law, 2022)
The aim of the article is to demonstrate that economic, technological and social changes, also thanks to the principle of sustainable development, lead to the transformation of existing and the emergence of new hybrid forms of conducting business activity. On one hand, there is a noticeable expansion of social economy mechanisms that reflect an ‘economic’ approach to providing broadly defined goods and services in the public interest, and there is also resurgence of democratic member-based organizations (DMOs), such as cooperatives with their dual nature and social and economic dimensions. On the other hand, traditional forms of for-profit business are transforming into entities that integrate social and environmental goals into business, known as Sustainability-Driven Hybrid Business Models (SHBMs), and of which benefit corporations (like U.S. Benefit Corporation or Social Purpose Corporation, Italian Societ. Benefit or French Soci.t. . mission) are an example. The transformation and emergence of these qualitatively new organizations is an illustration of the process of creative destruction described by Joseph Schumpeter. The article presents advantages and disadvantages associated with the benefit corporations. The analysis is concluded with the open question of whether legislative intervention is needed in this area, in particular whether it would be expedient to introduce ‘mission companies’ in Poland.